2002
DOI: 10.1056/nejmsa020969
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Activated Protein C Treatment for Severe Sepsis

Abstract: Activated protein C is relatively cost effective when targeted to patients with severe sepsis, greater severity of illness (an APACHE II score of 25 or more), and a reasonable life expectancy if they survive the episode of sepsis. Further research is needed to determine the cost effectiveness of activated protein C for patients with sepsis and less severe illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
3
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(104 citation statements)
references
References 26 publications
3
92
3
6
Order By: Relevance
“…CEACs can now be found in major medical journals such as BMJ [1][2][3][4][5], New England Journal of Medicine [6,7], Lancet [8], Circulation [9], Chest [10] as well as health economics and health technology assessment journals [11][12][13][14][15][16][17]. Given the widespread dissemination of this technique it is important to ensure that both analysts and potential users of the information understand the nature and interpretation of these curves.…”
Section: Introductionmentioning
confidence: 99%
“…CEACs can now be found in major medical journals such as BMJ [1][2][3][4][5], New England Journal of Medicine [6,7], Lancet [8], Circulation [9], Chest [10] as well as health economics and health technology assessment journals [11][12][13][14][15][16][17]. Given the widespread dissemination of this technique it is important to ensure that both analysts and potential users of the information understand the nature and interpretation of these curves.…”
Section: Introductionmentioning
confidence: 99%
“…Economic evaluations in several countries including the United Kingdom, France, Germany, Sweden, the United States, and Canada [30][31][32][33][34][35][36][37] show that APC is cost effective, on a short-term basis, in severe sepsis. Further, when APC is administered, according to the PROWESS criteria, to individuals with more severe disease (APACHE II score ≥25), it has a lifetime cost-effectiveness profile that compares well to that of many widely accepted therapies [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc analysis of the PROWESS data showed that although the relative risk (RR) of death for those with APACHE II scores of 25 or more was .71 and statistically significant, the RR for those with scores below 25 was a nonsignificant .99. 34 A subsequent study, ADDRESS, confirmed there was no benefit to septic patients with a low risk of death. 30 In the ADDRESS study 2613 patients with severe sepsis and either an APACHE II score less than 25 or single organ failure were randomized to APC or placebo.…”
Section: Activated Protein Cmentioning
confidence: 98%
“…34 Concerns have also been raised about the PROW-ESS trial itself: the production of the study drug and some exclusion criteria were changed midtrial, after which the effectiveness of APC improved. APACHE II scores had not been validated for selection of patients for therapies and may have varied with time or by observer.…”
Section: Activated Protein Cmentioning
confidence: 99%